Welcome To Death: Islamic And Catholic Perspectives (Al-Adyan: Journal of Religious Studies, 2021)
Death is one of the eschatological arenas in religions including Islam and Catholicism. Various things are done in preparation for welcoming death. This study was conducted to show how the two religions prepare their respective people to face it. This research relies on books and journals that examine the research topic from an Islamic and Catholic perspective. This research shows that in Islam, a good death is called husnul khatimah, namely dying in a state of being Muslim and doing good. For that, a Muslim must repent, maintain monotheism, keep the five daily prayers, pay zakat, fast in the month of Ramadan, make the pilgrimage if they are well-to-do, do what is required by religion and stay away from what is forbidden, have a noble character, guard the tongue. Meanwhile, according to Catholicism, human death is the result of human sin, good sinythat occurred as a result of the fall of the first human (Adam) as well as the sins committed by every human in the world. Therefore Catholicism teaches that prepare the kids to live independently, have character and education the good one; keep the way life and healthy so as not to bother children; financial preparation both for myself and children, keep the testimony alive, and have social relations good; inherent value and noble traditions in children and grandchildren.Kematian adalah salah satu arena eskatologis dalam agama-agama termasuk dalam Islam dan Katolik. Berbagai hal dilakukan sebagai persiapan untuk menyambut kematian. Studi ini dilakukan untuk memperlihatkan bagaimana kedua agama mempersiapkan umat masing-masing dalam menghadapinya. Penelitian ini bertumpu pada buku-buku dan jurnal yang mengkaji topik penelitian dimaksud dari perspektif Islam dan Katolik. Penelitian ini menunjukkan bahwa dalam Islam, kematian yang baik itu disebut dengan husnul khatimah yaitu mati dalam keadaan beragama Islam dan berbuat kebaikan. Untuk itu seorang muslim harus banyak bertaubat, menjaga tauhid, menjaga salat lima waktu, menunaikan zakat, berpuasa di bulan ramadhan, berhaji jika mampu, mengerjakan apa-apa yang telah diwajibkan oleh agama dan menjauhi yang dilarang, berakhlak mulia, menjaga lisan. Sedangkan menurut Katolik kematian manusia merupakan akibat dosa manusia, baik dosay yang terjadi akibat kejatuhan manusia pertama (Adam) maupun dosa yang dilakukan oleh setiap manusia di dunia. Untuk itu agama Katolik mengajarkan agar menyiapkan anak-anak hidup mandiri, memiliki karakter dan pendidikan yang baik;  menjaga cara hidup dan kesehatan agar tidak merepotkan anak-anak; menyiapkan finansial baik untuk diri sendiri maupun untuk anak-anak; menjaga kesaksian hidup, dan memiliki  relasi sosial yang baik; mewariskan nilai dan tradisi luhur pada anak dan cucu.